2010
DOI: 10.1016/j.mito.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Multistep and multitask Bax activation

Abstract: Bax is a pro-apoptotic protein allowing apoptosis to occur through the intrinsic, damage-induced pathway, and amplifying that one occurring via the extrinsic, receptor mediated pathway. Bax is present in viable cells and activated by pro-apoptotic stimuli. Activation implies structural changes, consisting of exposure of the N terminus and hydrophobic domains; changes in localization, consisting in migration from cytosol to mitochondria and endoplasmic reticulum membranes; changes in the aggregation status, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 132 publications
(143 reference statements)
1
47
0
4
Order By: Relevance
“…Interestingly, more than 75% of Bax colocalizes with mitochondria during apoptogenic insults, whereas the remaining Bax translocates to nuclei and endoplasmic reticulum or exists unbound in the cytosol (2). Bax lacks a mitochondrial localizing sequence, and a mitochondrial Bax receptor has yet to be identified (3,4), complicating efforts to dissect the molecular signals that drive intracellular Bax movement and toxicity. The possibility that a molecular chaperone facilitates mitochondrial Bax accumulation has been entertained recently (5,6).…”
mentioning
confidence: 99%
“…Interestingly, more than 75% of Bax colocalizes with mitochondria during apoptogenic insults, whereas the remaining Bax translocates to nuclei and endoplasmic reticulum or exists unbound in the cytosol (2). Bax lacks a mitochondrial localizing sequence, and a mitochondrial Bax receptor has yet to be identified (3,4), complicating efforts to dissect the molecular signals that drive intracellular Bax movement and toxicity. The possibility that a molecular chaperone facilitates mitochondrial Bax accumulation has been entertained recently (5,6).…”
mentioning
confidence: 99%
“…Such sharing of these pathways reflects and explains the coexistence of apoptosis and necrosis in APAPinduced liver injury. Bax is a pro-apoptotic protein allowing apoptosis to occur through the intrinsic, damage-induced pathway, and amplifying one occurring via the extrinsic, receptor-mediated pathway [10]. Bax protein is activated and translocates from the cytosol to the outer mitochondrial membrane, forming high conductance channels [1,10].…”
Section: Resultsmentioning
confidence: 99%
“…For immunohistochemistry, mouse monoclonal antibodies for Bax (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, U.S.A.), PRL (prepared as described previously [10]), HEL (Nikken Seil Co., Ltd., Shizuoka, Japan), 4-HHE-histidine (NOF Corporation, Tokyo, Japan) and CRA-lysine (NOF Corporation, Tokyo, Japan) were used as the primary antibodies. All sections were dewaxed, rehydrated, rinsed with 0.05 M tris-buffered saline (TBS; pH 7.6), treated with 3% hydrogen peroxide, and then rinsed again with TBS.…”
Section: Methodsmentioning
confidence: 99%
“…3) are the ones better characterized in molecular terms (Fulda & Debatin, 2006). The role of mitochondria as principal crossroad of the apoptotic process and emerged since 1990's, when it was shown that mitochondria of apoptosing cell death (Ghibelli & Diederich, 2010). The intrinsic pathway is characterized by the rapid release of cytochrome c from the mitochondrial inner membrane space into the cytosol.…”
Section: A Camphorata Regulates Apoptosis and Cell Survivalmentioning
confidence: 99%
“…During the stimulation, cytochrome c nucleates the assembly of a multi-protein complex, known as apoptosomes, functionally analog to the DISC, further recruits and activates the other upstream caspases, including caspase-9 and caspase-8. Caspase-8 and caspase-9 converge into proteolytic activation of caspase-3, results cells undergo execution phase of apoptosis and/or cell dismantling (Ghibelli & Diederich, 2010 (Yang et al, 2006;Yang et al, 2011). Meanwhile, the highest dose of A. camphorata (>100 µg/mL) was used to treat normal human endothelial cells for 24 hours, there was no cytotoxic effects were found.…”
Section: A Camphorata Regulates Apoptosis and Cell Survivalmentioning
confidence: 99%